Thrust Versus Non-Thrust Chuna Manipulative Therapy for Low-Back Pain with Pelvic Deviation: A Multicenter Feasibility Randomized Controlled Trial - Yeong-Jae Shin; Sun-Young Park; In-Hyuk Ha; Jun-Su Jang; Mi Hong Yim; Boncho Ku; Sanghun Lee; Hae Sun Suh; Yeon-Woo Lee; In Heo; Man-Suk Hwang; Eui-Hyoung Hwang; et al. (Healthcare, 2026)
Background/Objectives: Low-back pain (LBP) is a common musculoskeletal disorder, with a lifetime prevalence reported to be as high as 84%. Chuna manipulative therapy (CMT), a Korean style of manual therapy for correcting joint misalignment, has rarely been evaluated in randomized controlled trials (RCTs). This study primarily aimed to evaluate the feasibility of a future large-scale, multicenter RCT comparing thrust and non-thrust CMT; preliminary clinical and safety data were collected as secondary, exploratory objectives. Methods: This multicenter, assessor-blinded pilot RCT randomized 30 participants with non-acute LBP and pelvic deviation into thrust (n = 15) or non-thrust (n = 15) CMT groups for a 4-week treatment. Feasibility outcomes (eligibility, recruitment, adherence, retention, data completeness, and treatment fidelity) were the primary endpoints. Preliminary clinical effects (Numeric Rating Scale (NRS), Oswestry Disability Index (ODI)) and adverse events were assessed over 24 weeks as exploratory outcomes. Results: Of the 35 screened, 30 (85.7%) were randomized, and the planned 15 per center was achieved at both sites. Twenty-nine (96.7%) received at least the minimum number of sessions and were retained to week 24, with complete outcome data and no protocol deviations in intervention delivery. In exploratory analyses, both groups improved from baseline and between-group differences favored thrust CMT, but as the trial was not powered to compare effectiveness, these findings are preliminary only. Nine mild adverse events resolved spontaneously. Conclusions: A large-scale, multicenter RCT comparing thrust and non-thrust CMT in pelvic deviation is feasible. The observed feasibility outcomes can inform its progression criteria, whereas the exploratory clinical findings require confirmation in an adequately powered definitive trial.